The Test Bed Island: Tech Business Experimentalism and Exception in Singapore. (3rd July 2021) - Laurent, Brice; Doganova, Liliana; Gasull, Clément; Muniesa, Fabian
ABSTRACT: Islands imaginaries are imaginaries of exception, in the dual sense that islands are seen as places like no others (exceptional territories) as well as sites of exceptions to known orders of things (territories of exceptions). In Singapore, these two modalities of exception play a key role in Smart Nation, a program launched by the government in 2014 which shapes the island as an exceptional place for technology-oriented experiments meant for business development. We call this type of experimental practice tech business experimentalism . We investigate how the Smart Nation innovation program, conceived of as an example of tech business experimentalism, defines Singapore as an exceptional territory and a territory of exceptions. By studying how turning the island into a test bed relies on a politics of exceptionality, we show that current analyses of experiments beyond the scientific laboratory have much to gain by examining two related aspects, namely the business orientation of experiments and the exceptions on which they are built. This approach allows us to discuss the transformation of Singapore's territory, the processes whereby certain inhabitants (and not others) are turned into experimental subjects, and the re-definition of policy action as an ability to carve out material and regulatory exceptions.